UTILIZATION OF THE AL-BASED ISLAMIC ACCOUNTING INFORMATION SYSTEM AS A SOLUTION FOR TRANSPARENCY AND EFFECTIVENESS IN FINANCIAL MANAGEMENT OF MSMES - R, Fransisca Dwi; Sari, Nadila Adinda; Munawaroh, Miratul; Putri, Fara Evalia (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 11 No 1 (2025): The 11th International Conference of Islamic Economics and Business (ICONIES 2025), 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in the Indonesian economy, but they still face challenges in financial management, particularly related to transparency and effectiveness of financial reporting. The purpose of this study is to examine the use of an Artificial Intelligence (AI)-based Accounting Information System (AIS) with a sharia approach as a solution to increase transparency and effectiveness of MSME financial management. The research method used is a literature study by conducting an in-depth analysis of relevant literature and sources. The results of the study indicate that the implementation of an AI-based AIS can automate recording, improve the quality of financial reports, and support more appropriate decision-making, while the integration of sharia accounting principles ensures the alignment of financial governance with Islamic values. The main obstacles identified are limited human resources, implementation costs, and uneven technological infrastructure. The AI-Based Islamic Accounting System is presented as an innovative solution that supports MSMEs in increasing transparency and effectiveness of financial management in a sustainable manner, while still prioritizing sharia accounting principles.